LINE-1 methylation status and survival outcomes in colorectal cancer patients: A systematic review and meta-analysis - Akbar Bagheri; Tohid Jafari-Koshki; Leila Alizadeh; Mortaza Raeisi; Yaghoub Moaddab; Abbas Karimi (Heliyon)
Colorectal cancer (CRC) is a leading cause of cancer-related mortality worldwide. DNA hypomethylation, particularly of Long Interspersed Nuclear Element-1 (LINE-1) repetitive sequences, has been implicated in CRC development and progression. The purpose of this meta-analysis and systematic review was to evaluate the prognostic value of LINE-1 methylation level in patients with CRC. Relevant studies were identified through systematic database searches, and summary hazard ratios (HRs) with 95 % confidence intervals (CIs) were calculated for relations between LINE-1 hypomethylation and overall survival (OS), disease-free survival (DFS), and cancer-specific survival (CSS). The current systematic review protocol was registered on International Prospective Register of Systematic Reviews (PROSPERO, CRD42024496615). A total of 19 studies comprising 8169 CRC patients were included. The pooled analysis showed no significant association between LINE-1 hypomethylation and OS in the overall population (HR = 1.70, 95 % CI: 0.97–2.96). However, in stage II/III patients, LINE-1 hypomethylation was significantly associated with poorer OS (HR = 1.92, 95 % CI: 1.26–2.91) and DFS (HR = 2.81, 95 % CI: 1.33–5.93). No significant association was found between LINE-1 hypomethylation and CSS (HR = 1.39, 95 % CI: 0.68–2.83). Substantial heterogeneity was observed across studies. The study suggests that LINE-1 methylation level could be a valuable prognostic biomarker for advanced-stage CRC patients, potentially improving personalized care and highlighting areas for future research to establish standardized methodologies.